Sample Submission Guide for Plant Diagnostic Clinics of the Florida Plant Diagnostic Network. - Aaron J. Palmateer; Carol M. Stiles; Pamela D. Roberts; Richard E. Cullen; H. Dankers; Robert J. McGovern; Natalia Peres; Philip F. Harmon; Carrie L. Harmon (EDIS)
Revised! RF-SR007, an 8-page guide by A.J. Palmateer, C.M. Stiles, P.D. Roberts, R.E. Cullen, H. Dankers, R.J. McGovern, N. Peres, P.F. Harmon, and C.L. Harmon, provides extension clientele with the information they need to submit plant samples to Florida Extension Plant Diagnostic Clinics. Published by the UF Department of Plant Pathology, May 2008.